Strategy Adaptation Public Cultivator - Rajab, Muhammad (Greenation International Journal of Law and Social Sciences, 2023)
This paper was written based on research that describes the adaptation strategies carried out by cultivating communities. The majority of the people work as cultivators which is their main livelihood. However, there are several obstacles they encounter in farming, such as weather conditions, the slope of the land, the distance to the market place, and limited farming tools. This study aims to explain the adaptation strategies carried out by cultivating communities. The theory used in this research is the adaptation strategy theory introduced by Conklin (1954). Data collection was carried out by means of passive participatory observation, in-depth interviews and documentation studies. The research findings show knowledge of adaptation strategies developed by cultivating communities: First, adaptation strategies to the natural environment. Second, the adaptation strategy knowledge system that was carried out to the limitations of technological tools in farming was carried out by making tools from natural materials, namely Sungkaik and coffee grinders or gulunguih.